Reconstruction of proto-type basin and tectono-paleogeography of Tarim block in early Paleozoic - Zhong, Ziqi; Xia, Jinkai; Huang, Shaoying; Luo, Caiming; Chang, Haining; Li, Xiang; Wei, Lunyan; Zhang, Hao (Frontiers in Earth Science, 2023)
Tarim Basin is a large, superimposed basin rich in petroleum resources, which has experienced many stages of complex tectonic-sedimentary evolution. As the basic geological study of the Tarim Basin, the proto-type basin and tectono-paleogeographic evolution are of great significance for understanding the distribution of petroleum reservoirs in the superimposed basin and provide tectonic background and theoretical guidance for petroleum exploration. According to the residual thickness map, as well as other lithofacies and seismic data, the scopes of the proto-type basin are determined by the marginal facies method and the thickness trend method, and the shortening amounts are calculated by the balanced cross-section method. Based on these data and previous works, four proto-type basin maps of Tarim Basin in present-day geographic coordinates and four tectono-paleogeographic maps of Tarim Basin in paleogeographic coordinates during the early Paleozoic are reconstructed, which directly show the changes of sedimentary and uplift-depression pattern caused by the transformation of the tectonic environment from extension to compression. In the Cambrian, the Tarim Basin was controlled by the extensional tectonic environment, with the sedimentary framework of "carbonate platform in the west, deep-water basin in the east". At the end of the Ordovician, the Kudi Ocean and the North Altyn Ocean were closed, and the Central and South Kunlun terrane and the Altyn-Qilian terrane were collaged with the Tarim block, which directly led to the transformation of the uplift-depression pattern in the Tarim Basin from east-west differentiation to north-south differentiation, thus changing the sedimentary environment of the Tarim Basin in the late Ordovician to Silurian.